BALINESE TRADITIONAL LANDSCAPE - Yudantini, Ni Made (Jurnal Natah; Vol. 1, No. 2 Juni 2003, 2012)
Balinese traditional landscape defend is an important effort to preseve a vernacular traditional landscape, which is can give calamity, beauty, peaceful, comfort feeling, for healthy, happiness as well as to give Balinese identity. It is also supported by the government program of “ Bali to head for Garden Island”. Principally, Balinese traditional landscape is soul by the philosophy of Balinese culture such as Tri Hita Karana concept, Rwa Bhineda concept, Desa Kala Patra concept, Sekala Niskala concept, etc. Structurally, Balinese traditional landscape can divide into five types as follows Regional landscape, Villages landscape, City landscape, highway landscape and Inheritance Garden. Balinese landscape can begin firstly through the landscaping in the house, where we can placed the garden. The most uniqueness of landscape in the traditional housing of Bali, there are including natah as an orientation of buildings, its garden, back yard/teba, lebuh and telajakan.
Keywords: Balinese Traditional Landscape, Concept.